2016
DOI: 10.1016/j.ecolind.2015.11.041
|View full text |Cite|
|
Sign up to set email alerts
|

International inequality of environmental pressures: Decomposition and comparative analysis

Abstract: Natural resource scarcity is no longer merely a remote possibility and governments increasingly seek information about the global distribution of resource use and related environmental pressures. This paper presents an international distributional analysis of natural resource use indicators. These encompass both territorial (national production) and footprint (national consumption) indicators for land-related pressures (human appropriation of net primary production, HANPP, and embodied HANPP), for material use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 70 publications
1
47
0
Order By: Relevance
“…The literature shows many examples of the Gini coefficients and Lorenz curves being used for assessing the inequality of domains other than income, such as: house size (Kohler et al 2017), happiness (Bennett and Nikolaev 2017) solid waste arising from material resource use (Druckman and Jackson 2008), historical (Groot 2010) and future (Zimm and Nakicenovic 2019) carbon emissions, material indicators (e.g. domestic extraction, domestic material consumption and material footprint) and indicators measuring the intensity with which human society uses terrestrial ecosystems (Teixidó-Figueras et al 2016), education (Sauer and Zagler 2014;Vinod, Yan, and Xibo 2001), health (Williams and Cookson 2000), spatial inequity in transportation (Jang et al 2017), internet bandwidth (Hilbert 2016), mobile phones, radios and bikes (Bento 2016), energy (Wu, Zheng, and Wei 2017) and electricity (Jacobson, Milman, and Kammen 2005).…”
Section: Gini Coefficient and Lorenz Curvementioning
confidence: 99%
“…The literature shows many examples of the Gini coefficients and Lorenz curves being used for assessing the inequality of domains other than income, such as: house size (Kohler et al 2017), happiness (Bennett and Nikolaev 2017) solid waste arising from material resource use (Druckman and Jackson 2008), historical (Groot 2010) and future (Zimm and Nakicenovic 2019) carbon emissions, material indicators (e.g. domestic extraction, domestic material consumption and material footprint) and indicators measuring the intensity with which human society uses terrestrial ecosystems (Teixidó-Figueras et al 2016), education (Sauer and Zagler 2014;Vinod, Yan, and Xibo 2001), health (Williams and Cookson 2000), spatial inequity in transportation (Jang et al 2017), internet bandwidth (Hilbert 2016), mobile phones, radios and bikes (Bento 2016), energy (Wu, Zheng, and Wei 2017) and electricity (Jacobson, Milman, and Kammen 2005).…”
Section: Gini Coefficient and Lorenz Curvementioning
confidence: 99%
“…Extraction has the greatest diversity due to the skew distribution of fossil fuel resources. Fossil fuel trade causes a smoother distribution in production based emissions, and trade in goods and services causes an even smoother distribution for consumption (Teixidó-Figueras et al 2016). Table 1 illustrates these distributions of cost and revenue for extractors, producers and consumers when implemented at different points in the supply-chain.…”
Section: Carbon Price Cost and Revenue Distributionsmentioning
confidence: 99%
“…After the study of Theil [18] in the field of income inequality, the vast literature of environmental inequality studies has emerged. Some of these studies have applied the Theil index to measure CO 2 emission inequality globally (see, e.g., [50,[70][71][72][73][74]), exposure to industrial pollution [7], or health disparity [75].…”
Section: The Empirical Methodologymentioning
confidence: 99%
“…Fecht et al [12] indicated urbanization as one important cause of air pollution inequality in exposure to NO 2 in England and Netherlands. Teixidó-Figueras et al [50] consider urbanization as one of the factors which create global environmental inequality because of activities requiring more resources. Knill et al [51] found that rapid urbanization can increase NO X emission in OECD countries.…”
Section: Urban Development Disparity and No X Emissionmentioning
confidence: 99%